Guest Editor's Introduction: Practitioners of Action Research in International Educational Settings - David Alan Sapp (Networks: An Online Journal for Teacher Research, 2002)
This special issue of Networks focuses on "Action Research in International (non-North American) Educational Settings" and brings together work by practitioners from several educational settings such as Spain, Turkey, Bulgaria, and Hawaii. In these articles, the authors explore the challenges, experiences, and promises of increased globalization in education. This work includes case studies focusing on specific teaching experiences as well as critical descriptions of the lives and values of action researchers in international contexts.